A comparative analysis on tensile strength of dry and moisture absorbed hybrid kenaf/glass polymer composites. (May 2018) - Praveen Kumar, A; Nalla Mohamed, M
Economic and environmental concerns lead the researchers toward development of sustainable and renewable materials of which reinforced composites are part of. The abundantly available natural fibers have attracted the researchers to study their performance as reinforcements and feasibility for making automobile components. The performance of composite materials is mainly assessed through their mechanical properties. However, natural fibers to date were mainly used as reinforcements to create bulk composite components with reduced cost rather than improved mechanical performances. Among the methods available for improving mechanical properties of the natural fiber composites, combined mercerization treatment, hybridization, and incorporation of fly ash fillers in the matrix are the best solutions. Therefore, the objective of this research is to evaluate the tensile properties of hybrid kenaf/glass composites with and without fly ash particulate filler as per ASTM standards. Moisture absorption behavior and its effect on the tensile properties of hybrid composites are also investigated. The results revealed that the addition of 10wt % fly ash particles with natural fiber composites increased the tensile strength of composites while hybridization with glass fibers reduced the water absorption properties.